An efficient successive relaying protocol for multiple-relay cooperative networks - Li, Kwok Hung (2013)
We propose an efficient successive relaying (SR) transmission protocol for multiple-relay cooperative systems under the half-duplex constraint. In this protocol, the process of relay selection is conducted once the instantaneous channel state information changes. During each channel coherent interval, the source keeps transmitting newly generated messages, and two selected relays successively decode and forward the source's information to the destination. In particular, in one time slot, a selected relay jointly decodes both signals transmitted from the source and the other selected relay. In the next time slot, this relay forwards the superposition of these two decoded signals. The destination jointly decodes messages at the end of each interval. The lower bound of outage probability is derived in a closed-form expression and the diversity-multiplexing trade-off (DMT) performance is characterized as well. It is demonstrated by the numerical results that the proposed SR protocol is capable of achieving both full diversity gain and high multiplexing gain.